Rantai Nilai, Corporate Farming Dan Nilai Tambah Komoditas Kopi Kabupaten Temanggung - Matruty, Eko Suseno HR; Widodo, Arief; Damayanti, Theresia Woro; Supramono, Supramono (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2023)
D Research aim: To analyze the coffee commodity value chain and (b) to analyze the opportunities and challenges of implementing coffee commodity corporate farming in Temanggung Regency Design/Methode/Approach: Data were obtained through interviews with several farmers, direct observations in the field, and FGDs involving the Temanggung Regency government apparatus related to the development of coffee commodities. Data are analyzed in narrative form, value chain analysis, and corporate farming model Research Finding: The study results show that the coffee commodity value chain in Temanggung Regency consists of input, production, collection, processing, and marketing or distribution to consumers. Each of these chains has its problems, from the smooth supply of inputs and production prices, ​​land ownership, and picking/harvesting coffee cherries that do not meet quality standards to coffee marketing. From the results of the FGD, it was also revealed that corporate farming has the opportunity to be applied to deal with the problem of coffee commodities so that it is expected to create higher added value which will be enjoyed by the farmers of Temanggung Regency Theoretical contribution/Originality: This study integrates value chain analysis with the corporate farming model, which has not been the concern of previous researchers Practitioner/Policy implication: This study offers policy proposals to the Temanggung Regional Government regarding the formation of corporate farming so that it can run effectively Research limitation: Not yet analyzed based on a quantitative approach, especially related to feasibility aspects.